1. Introduction: Why Another Study on COVID-19 and Youth? Introduction to the YO-VID22 Project Main Publication - Naterer, Andrej; Potočnik, Dunja (Two Countries, One Crisis: The YO-VID22 Pandemic Study, 2025)
The introductory chapter outlines the methodological design and rationale of the YO-VID22 project, which investigated the impact of the COVID-19 pandemic on youth well-being and support structures in Croatia and Slovenia. Employing a mixed-method approach, the study combined large-scale quantitative nationally representative surveys with qualitative methods, which included focus groups, expert interviews, and media content analysis. Quantitative data were collected through stratified online surveys on nationally representative samples of 16-29-year-olds, which enabled comparisons with pre-pandemic datasets. Qualitative components provided more profound insights into lived experiences, institutional responses, and public discourse surrounding youth. Focus groups captured peer-based dynamics and shared cultural values, while expert interviews highlighted systemic adaptations and policy gaps. At the same time, media analysis revealed shifting portrayals of young people in the public sphere. This integrated research design ensured both statistical robustness and contextual richness, and offered comprehensive evidence for understanding youth experiences during the pandemic and informing future policy and academic debates.